Legal pluralism explained history, theory, consequences - Tamanaha, Brian Z. (Oxford University Press, 2021)
Throughout the medieval period law was seen as the product of social groups and associations that formed legal orders, as Max Weber elaborates, "either constituted in its membership by such objective characteristics of birth, political, ethnic, or religious denomination, mode of life or occupation, or arose through the process of explicit fraternization." During the second half of the Middle Ages, roughly the tenth through fifteenth centuries, there were "several distinct types of law, sometimes competing, occasionally overlapping, invariably invoking different traditions, jurisdictions and modes of operation." Types of law included imperial and royal edicts and statutes, canon law, unwritten customary law of tribes and localities, written Germanic law, residual Roman law, municipal statutes, the law of merchants and of guilds, and in England the common law, on the continent the Roman law of jurists after the twelfth century revival of the Justinian Code. The types of courts included various imperial and royal courts, ecclesiastical courts, manorial or seigniorial courts, village courts, municipal courts in cities, merchant courts, and guild courts. Serving as judges in these courts, respectively, were kings or their appointees, Bishops and abbots, barons or lords of the manor or their appointees, local lay leaders, leading burghers, merchants, and members of the guild. These various positions were not wholly separate-many high government officials were in religious orders, while Churches held landed estates that came with local judicial responsibilities. "Bishops, abbots and prioresses, as lords of temporal possessions, controlled manorial or honorial courts at which they sometimes, though not generally, presided in person, exercising responsibility for criminal and customary law." "The result was the existence of numerous law communities," Weber wrote, "the autonomous jurisdictions of which overlapped, the compulsory, political association being only one such autonomous jurisdiction in so far as it existed at all." Jurisdictional rules for judicial tribunals and the laws to be applied related to the persons involved and the subject matter at issue. The personality principle linked law to a person's community or association, and under feudalism property ownership came wrapped together with the right to judge those tied to the property. "Demarcation disputes between these laws and courts were numerous." Jurisdictional conflicts arose especially in relation to ecclesiastical courts, which claimed broad jurisdiction over personal status laws (marriage, divorce, inheritance) and moral crimes, as well as church property and personnel, matters which regularly overlapped with the jurisdiction of other courts. Furthermore, different bodies of law could be applicable in a given court in a given case. "It was common to find many different codes of customary law in force in the same kingdom, town or village, even in the same house, if the ninth century bishop Agobard of Lyons is to be believed when he says, 'It often happened that five mem were present or sitting together, and not one of them had the same law as another.'" In long settled areas, the personal law of communities became local customary law. People living within cities were subject to municipal statutes and customary law on certain matters (penal law, procedural), and the community law to which they were attached"--